Review of Health Economics of Point-of-Care Testing Worldwide and Its Efficacy of Implementation in the Primary Health Care Setting in Remote Australia - Wong HY; Marcu LG; Bezak E; Parange NA (Dove Medical Press, 2020)
Hoi Yan Wong,1 Loredana G Marcu,2,3 Eva Bezak,1,3,4 Nayana Anupam Parange1,3 1Division of Health Sciences, University of South Australia, Adelaide, SA 5000, Australia; 2Faculty of Informatics & Science, University of Oradea, Oradea 410087, Romania; 3Cancer Research Institute and School of Health Sciences, University of South Australia, Adelaide, SA 5001, Australia; 4Department of Physics, University of Adelaide, Adelaide, SA 5005, AustraliaCorrespondence: Nayana Anupam Parange Tel +61 8302 2585Email nayana.Parange@unisa.edu.auAbstract: There are important differences concerning health outcomes between the Australian population living in rural/remote regions and the urban population. Health care provision in remote areas, particularly in regions with a low number of inhabitants, is not without challenges. Aboriginal, rural and remote communities are therefore affected, as they face various obstacles in accessing health services, owing to geographical settings, difficulties in transportation to nearby hospitals, limited or inexistent local qualified personnel. The implementation of point-of-care testing could be a plausible solution to these challenges, as various point-of-care services that have been successfully put into action worldwide indicate towards positive clinical outcomes. Point-of-care units have a real potential in reducing morbidity and mortality in all population groups. This article aims to review the published literature on point-of-care testing around the world, with a focus on health economics and the feasibility of its implementation in Australian rural and remote regions.Keywords: health economics, remote areas, point-of-care testing, cost-effectiveness